Mechanisms of exercise for diabetic neuropathic pain - Luo, Jing; Zhu, Hui-Qi; Gou, Bo; Zheng, Yi-Li (Frontiers in Aging Neuroscience, 2022)
Diabetic neuropathic pain (DNP) is a common disease that affects the daily lives of diabetic patients and its incidence rate worldwide is very high. At present, drug and exercise therapy are common treatments for DNP. Drug therapy has various side effects, and in recent years, exercise therapy has received frequent research and increasing attention. Currently, the treatment of DNP is generally symptomatic. We can better select the appropriate exercise prescription for DNP only by clarifying the exercise mechanism for its therapy. The unique pathological mechanism of DNP is still unclear and may be related to the pathological mechanism of diabetic neuropathy. In this paper, the mechanisms of exercise therapy for DNP from the pathological mechanism of DNP were reviewed to better understand the role of exercise therapy in treating DNP.